2015
DOI: 10.1002/job.2061
|View full text |Cite
|
Sign up to set email alerts
|

Got milk? Workplace factors related to breastfeeding among working mothers

Abstract: SummaryThe American Academy of Pediatrics recommends that women breastfeed because of improved health outcomes for mothers and children. Because maternal employment during the first year of the child's life has been identified as a reason for breastfeeding cessation, we develop and test a role-theory-based framework to explain women's continuation of breastfeeding after return to work (Study 1) and report results of an exploratory study linking breastfeeding at work with job attitudes and well-being (Study 2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 69 publications
2
47
0
2
Order By: Relevance
“…Although men and women do not differ in management capabilities, and women show natural higher empathy capabilities, there is still a sexual division of labor, with productive work outside the home belonging to men and the tasks of the reproduction function and unpaid labor belonging to women (Goldscheider, Bernhardt & Lappegard, ; Joshi, Neely, Emrich, Griffiths & George, ). There is little evidence that the workplace has changed to better enable men to reconcile work and family responsibilities (Spitzmueller, Wang, Zhang et al, ). Men's uptake of work‐family reconciliation policies would alter the pattern of gender inequality in family life and in the labor market (Maume, ), as well as potentiating their management skills at workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Although men and women do not differ in management capabilities, and women show natural higher empathy capabilities, there is still a sexual division of labor, with productive work outside the home belonging to men and the tasks of the reproduction function and unpaid labor belonging to women (Goldscheider, Bernhardt & Lappegard, ; Joshi, Neely, Emrich, Griffiths & George, ). There is little evidence that the workplace has changed to better enable men to reconcile work and family responsibilities (Spitzmueller, Wang, Zhang et al, ). Men's uptake of work‐family reconciliation policies would alter the pattern of gender inequality in family life and in the labor market (Maume, ), as well as potentiating their management skills at workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these concerns still are relevant today not only in regard to parental leave policies but even with FWAs, as some fear that these employees are left to "pick up the slack" when those with family-related responsibilities use flextime provisions (Bagger & Li, 2014: 1146. Most recently, these perceptions of unfairness have been extended to other on-site provisions, such as breastfeeding rooms for nursing mothers (Spitzmueller et al, 2016). Relatedly, Li et al (2015) indicate that employees with elder caregiving responsibilities might come to resent the childcare provisions of their organization because the caregiving provisions are not comprehensive enough to suit their needs.…”
Section: Strategic Responses To Institutional Theorymentioning
confidence: 99%
“…Unlike the inequity mechanism, however, it applies to both men and women in different ways and thus has gender-based implications. For example, only women are subject to endure negative remarks and jokes made about the use of on-site breastfeeding rooms, including comments about the length of time these breaks take (Spitzmueller et al, 2016). Similarly, women are required to deal with the pregnancy stigma and "mommy track" careers, as they face decisions about whether to have children and when and how to disclose their pregnancy (Jones, 2017;Jones et al, 2016;Little et al, 2015).…”
Section: Mechanism 2: Stigmamentioning
confidence: 99%
“…Our study outcome showed that children of working women were 11.4% more likely to die than the children of not working women. Working women have less time to look after their children due to their professional demands [66]. Moreover, they also remain under-stress because of tiresome professional and personal duties [67], leading to the risk of child mortality.…”
Section: Descriptive Statisticsmentioning
confidence: 99%